Evaluación de la creación literaria: de la racionalidad técnica tradicional al enfoque crítico, formativo y artístico - Saavedra Rey, Alirio Sneider (Enunciación, 2010)
Based on the recognition of the evaluation importanceon the configuration of teaching and learning pro-cesses, this article of reflection, as a part of the researchTowards a formative, critical and artistic evaluation ofliterary creation, analyzes the development of theseeducational practices from the technical rationality,based on the conception of literature and languageas normative systems. Because of the fact that thesepractices circumscribe the discursive construction ofpossible worlds with the aesthetic purpose involved inthe literary, it is proposed a both evaluative and educa-tional approach since the postulates of the formative,critical and artistic evaluation.